2013
DOI: 10.7763/ijesd.2013.v4.345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Composition and the Preparation Methods on Oil Sorption Capacity of Recycled Rayon Waste-Kapok Mixtures (RRWK) Sorbent

Abstract: Abstract-The aim of this study was to investigate the utilization of a recycled rayon waste-kapok mixtures as an oil sorbent for the removal of diesel, motor oil and bunker C. The effects of the kapok fibers: rayon fibers ratio and the additional of sodium sulfate on RRWK sorbents properties were investigated through series of oil sorption tests. The ASTM 726-06 method was used to determine the oil sorption capacity of the sorbents under both static and dynamic conditions. The results showed the high sorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This means that the Langmuir model can be proper to describe the experimental data. Based on this model, it can be concluded that the active sites on the biosorbents surface were distributed in homogeneous form [19], and monolayer adsorption manner was dominant for sorption [20].…”
Section: Oil and Water Sorption By Unacetylated And Acetylated Biosor...mentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the Langmuir model can be proper to describe the experimental data. Based on this model, it can be concluded that the active sites on the biosorbents surface were distributed in homogeneous form [19], and monolayer adsorption manner was dominant for sorption [20].…”
Section: Oil and Water Sorption By Unacetylated And Acetylated Biosor...mentioning
confidence: 99%
“…The unacetylated biosorbent showed higher water uptake at 60 minutes compared to water uptake by the acetylated. The water uptake by the unacetylated leave was 9.15g/g which increases to 21.59g/g (figure 6), stem from 5.06g/g increases to 13.35g/g (figure 7) while root from 6.20g/g increases to 19.30g/g (figure 8) respectively. However, the water uptake for acetylated leave was 5.21g/g which increases to 14.33g/g (figure 6), stem from 2.23g/g increases to 10.35g/g (figure 7) while root from 3.23g/g increases to 16.32g/g (figure 8) respectively.…”
mentioning
confidence: 95%
“…Crude oil is one of the most important hydrocarbon fluids in modern world since it is the raw material for many industries, such as petrochemicals, fuels, and polymers . The use of oil and its products has globally increased to reach approximately 100 million tons/year.…”
Section: Introductionmentioning
confidence: 99%
“…Crude oil is one of the most important hydrocarbon fluids in modern world since it is the raw material for many industries, such as petrochemicals, fuels, and polymers. [1,2] The use of oil and its products has globally increased to reach approximately 100 million tons/year. Such huge production of oil and its related trading in bodies of water could leave behind a massive rate of oil-polluted water.…”
Section: Introductionmentioning
confidence: 99%
“…The processes involved in cleaning oil spill were normally very complicated and not environmentally friendly [2]. The treatment for oil spills including chemical, mechanical and biological treatments [3]. In mechanical treatment, absorbent of synthetic or natural materials is an effective cost saving option [4].…”
Section: Introductionmentioning
confidence: 99%